Single mode lasing from CsPbBr₃ microcrystals fabricated by solid state space-confined growth - Cheng, Shijia (2023)
All-inorganic metal halide perovskites, such as CsPbX3 (X = Br, Cl, or I), have attracted significant interest for a new generation of integrated, high-performance optoelectronic devices. To realize the full potential of layer-by-layer devices, perovskite crystal thin films are preferred over crystal ingots, considering carrier loss during carrier transport. The space-confined method is a facile way of fabricating perovskite crystal films in a geometrically confined space to break the isotropic growth. Many researchers have reported effective preparation of large-area perovskite films using this method. However, most space-confined methods require growth in a liquid phase (solution), which can cause uncontrollable nucleation, surface traps, and unsatisfactory device performance. In this work, a pure solid-state space-confined strategy to grow CsPbBr3 films for the first time without relying on solution conditions is developed. The regular shapes of CsPbBr3 films prepared by this solid-state space-confined strategy can function as effective multimode and single-mode Fabry–Perot (F–P) microlasers under optical pumping. This work overcomes the challenge that the conventional space-confined method can only be adapted to the liquid phase. It also opens a new approach for making high-quality microlasers, which are significant for photonic integrated circuits and optoelectronic devices.